2019
DOI: 10.2478/jomb-2018-0051
|View full text |Cite
|
Sign up to set email alerts
|

Decreased serum level of gamma-amino butyric acid in Egyptian infertile females with polycystic ovary syndrome is correlated with dyslipidemia, total testosterone and 25(OH) vitamin D levels

Abstract: Summary Background Polycystic ovary syndrome (PCOS) is one of the most common female endocrine disorders around the world. Increasing evidence suggests that neurotransmitter Gamma-aminobutyric acid (GABA) is involved in the pathogenesis of PCOS through its central role in the hypothalamus. However, the peripheral role of GABA in PCOS has not been sufficiently investigated in spite of its existence in peripheral organs. First, the aim of this study is to, investigate serum GABA level in Egyptian PCOS patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 56 publications
2
7
0
Order By: Relevance
“…Upon comparing PCOS patients to non-PCOS cases, we found that PCOS patients had significantly higher total testosterone, higher TC, and LDL-C together with significantly low levels of 25 (OH) vitamin D. The same profile was maintained upon comparing asthmatic PCOS patients to asthmatic patients with no PCOS. Such results are in accordance with previous studies (3, 17, 28) and they confirm the main findings of PCOS, where dyslipidemia is highly prevalent in PCOS even in lean females mostly due to insulin resistance (29). Whereas vitamin D deficiency has also been reported in PCOS patients (30), contributing to their disturbed metabolic profile.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Upon comparing PCOS patients to non-PCOS cases, we found that PCOS patients had significantly higher total testosterone, higher TC, and LDL-C together with significantly low levels of 25 (OH) vitamin D. The same profile was maintained upon comparing asthmatic PCOS patients to asthmatic patients with no PCOS. Such results are in accordance with previous studies (3, 17, 28) and they confirm the main findings of PCOS, where dyslipidemia is highly prevalent in PCOS even in lean females mostly due to insulin resistance (29). Whereas vitamin D deficiency has also been reported in PCOS patients (30), contributing to their disturbed metabolic profile.…”
Section: Discussionsupporting
confidence: 93%
“…Decreased levels of 25 (OH) vitamin D have been linked to increased risk of asthma attacks in asthmatic patients (23, 24, 28). Additionally, Vitamin D deficiency is known to be highly prevalent in PCOS patients (67–85%), where the deficiency is especially reported to worsen the symptoms of PCOS (29), including menstrual irregularities, cardiac disorders (33), obesity (34, 35) and deteriorating metabolic phenotype (36).…”
Section: Discussionmentioning
confidence: 99%
“…Although GABA is typically an inhibitory neurotransmitter, GnRH neurons respond to GABA with excitation due to higher intracellular chloride levels, 61 with DHT increasing GABA mediated stimulation of GnRH neurons. Peripheral circulating GABA levels were found to be reduced, 62 whereas central CSF GABA levels were increased, 63 in women with PCOS. Accordingly, medications that increase GABA, such as anti‐epileptic drugs, have been associated with an increased prevalence of PCOS 64 …”
Section: Introductionmentioning
confidence: 93%
“…Similarly, letrozole and testosterone-induced PCOS models showed reduced GABA levels in the hypothalamus (29, 30). Clinical observation also reports lower serum GABA levels in Egyptian infertile females with PCOS (52). With these observations, it could make sense that letrozole-fed mice had decreased GABA A receptor-mediated activity on GnRH neurons.…”
Section: Discussionmentioning
confidence: 83%